Dietary diversity among women of reproductive age (15-49 years): implication for folate deficiency in Mbarara district, Uganda - Tamale, Denison; Kagoro-Rugunda, Grace (International Journal Of Community Medicine And Public Health, 2019)
Background: Understanding dietary diversity of women of reproductive age (WRA) is vital for better nutritional interventions of their health and that of unborn. Most diets consumed are macronutrient dense which leads to micronutrient deficiencies like neural tube defects (NTDs).Thirty three babies were born with NTDs at Mbarara Regional Referral Hospital during 2016 and 2017 for reasons among which is folate deficiency. Folate can be derived cheaply from green vegetable consumption before antenatal visits. The study’s objective was to assess dietary diversity of WRA (15-49 years) living within Mbarara district. Methods: A cross sectional study was conducted for three months using a translated dietary diversity questionnaire from Food and Agricultural Organisation. Applying a 24 h recall method at various intervals of feeding, 402 WRA living within three constituencies of Mbarara district were randomly selected to participate. Results: 70.1% of WRA attained high Individual dietary diversity score (IDDS) of (≥6). 45.1% consumed folate rich plant and animal sources. 4.8%, 8.4%, and 17.6% consumed dark green leafy vegetables, vitamin rich fruits and animal sources respectively. Education, constituency of residence and occupation had a significant association with IDDS of P≤0.05 (0.000, 0.004, 0.030) respectively. WRA who scored IDDS≥6, 58.2% attained at least secondary education, 51.1% lived in urban constituency and 47.5% were working. 30% consumed starchy staple groups, though at 15.8% legumes, nuts and seeds group was most consumed. Conclusions: Low intake of folate rich sources was noted, though many WRA consumed diverse diets therefore, education and employment are suitable interventions.